Penerapan Algoritma Stout Codes Pada Kompresi File Audio Aplikasi Kumpulan Ceramah Ustadz KH. Zainuddin MZ - Hrp, Aziz Alfaridho (Journal Global Technology Computer, 2023)
At this time, technological developments play a very important role in facilitating the transfer of data, both audio and video, however, with the amount of data received not being balanced with the memory capacity that is available, making the memory work slowly or slowly, it is recommended to carry out a compression process first, especially on files that large capacity. Compression techniques are usually used for data transmission and data storage processes. The advantages of compressed data include saving data storage, making it easier to distribute data using electronic media or removable media such as flash disks, CDs, DVDs, etc. Based on the advantages above, this research applies a data compression algorithm to audio files using the stout code algorithm. The audio files of Ustadz KH. Zainuddin MZ's lectures are very popular so it would be very detrimental if the files were enjoyed in large files. Therefore, this research is very useful according to the author and it is hoped that it will also be useful for other users.